Effects of bovine spermatozoa preparation on embryonic development in vitro - Cergolj Marijan; Makek Zdenko; Getz Iva; Karadjole Martina; Samardzija Marko; Dobranic Tomislav (BMC, 2006)
Abstract The aim of our research was to examine the ability of density gradient preparation BoviPure® and swim up method on bull sperm separation and in vitro embryo production (IVP) systems. Frozen/thawed semen from six Simmental bulls was pooled and treated using both methods. The sperm motility, concentration, membrane activity, membrane integrity and acrosomal status were evaluated and compared before and after sperm processing using BoviPure® and swim up methods. We also evaluated and compared cleavage rates, embryo yield and quality between the methods. There were significant differences (P < 0.05) between the sperm characteristics before and after BoviPure®, but not after swim up method. However, there were significant differences for sperm results among those two mentioned methods. A total of 641 oocytes were matured and fertilized in vitro and cultured in SOFaaBSA. The percentage of cleavage (Day 2) and the percentage of hatched embryos (Day 9) were similar for both methods. However, embryo production rate (Day 7) was significantly higher using BoviPure® method (P < 0.05). Also, total cell number and embryo differential staining (inner cell mass and trophectoderm cells) of Day 7 morulas and blastocysts showed that BoviPure® treated sperm displayed higher quality embryos compared to swim up method (P < 0.05). Our results indicate that BoviPure® method has an enhanced capacity in sperm selection for in vitro embryo production when compared with swim up method. So, we concluded that BoviPure® could be considered as a better alternative to swim up method for separating bull spermatozoa from frozen/thawed semen for IVP of bovine embryos.